The Effect of Thelison Use in The Etiology of Lung Disorders among Homeless People - Alaa Aldin Alsafi Alalwiy; Alkhair Abd Almahmoud Idris (Cell and BioPharmaceutical Institute, 2022)
Background: Thelison, the adhesive synthetic material that bind surface together, is widely used in industry and domestic purpose along with epoxy, glue and putty. The aim of this study was to detect the effect of thelison use in the etiology of lung disorders among homeless people in Khartoum State, Sudan.Materials and method: This was a descriptive cross sectional study conducted in homeless people in Khartoum State.Sputum smears samples from 80 alcohol fixed homeless thelison user were collected. After the collection of the sample, Argyrophilic Nucleolar Organizer Region (AgNOR) technique and papanicolaou (PAP) stains were applied to each sample. A questionnaire to obtain essential data about respondents was also provided for each participant.Results: Participant’s ages range was 10-37, while the mean age was 17. The range of participants duration of use per years was 1-10, while the mean was 3 years. Number of thelesion dose use per day was ranged between 1-10, while the mean was 5 years. The majority of participants (80%) showed no cellular change and 20 % showed chronic inflammation. Results showed that 31 of the study population were males (77.5%), while the female population of the study was 9 (22.5%). The mean of AgNoR score was ranged between 1-4, while the mean AgNOR score was 1. AgNoR showed insignificant association with gender, duration and number of thelesion dose used per day (p>0.05), but showed significant association with cytomorhpological and age (p<0.05).Conclusion: AgNoR score showed insignificant association with gender, duration and number of thelesion dose used per day (p>0.05), but showed significant association with cytomorhpological and age (p<0.05).Keywords: AgNoRs score, cytological changes, sputum, homeless thelison users